Plant-growth-promoting rhizobacteria for mitigating salinity stress in rice farming: a review of the Vietnamese Mekong Delta - Nguyen, Trinh Thi My; Ha-Tran, Dung Minh; Huang, Chieh-Chen (Frontiers in Plant Science, 2025)
Salinity intrusion, exacerbated by climate change and anthropogenic activities, poses a significant global threat to agricultural productivity, particularly in coastal and deltaic regions. Rice, a staple crop critical for food security and economic stability in many developing nations, is highly susceptible to salt stress, which reduces yields and threatens livelihoods. In the Vietnamese Mekong Delta (VMD), a key rice-producing region, recurrent drought-induced salinity events have caused substantial damage to agriculture, and the economic well-being of millions of residents. These events highlight the urgent need for sustainable solutions to maintain rice production under adverse environmental conditions. Plant-Growth-Promoting Rhizobacteria (PGPR) have emerged as a promising eco-friendly approach to enhance plant salt tolerance, offering potential to mitigate salinity stress in rice crops. Here we review the role of PGPR in alleviating salinity stress in rice farming in the VMD, highlighting its potential as a sustainable agricultural approach. The review synthesizes existing research to assess the causes of salinity intrusion, the efficacy of PGPR, and the limitations of current studies in this region. The major points are the following: 1) Saline intrusion in the VMD is driven by multiple factors, including sea-level rise, land subsidence, upstream dams’ operation, and excessive sand mining, which exacerbate agricultural challenges; 2) PGPR enhance rice salt tolerance through mechanisms such as osmotic regulation, improved nutrient uptake, and activation of stress-responsive genes, as evidenced in controlled and field studies; 3) Research in Vietnam is constrained by a lack of long-term investigations and a reliance on publications in Vietnamese-language scientific journals, which may limit international attention and rigorous peer-review processes, necessitating further studies to support scalability and adoption by VMD farmers, and also enlarge international collaboration in this important field of study.